2008
DOI: 10.1002/chem.200701795
|View full text |Cite
|
Sign up to set email alerts
|

Gold Catalysis: Deuterated Substrates as the Key for an Experimental Insight into the Mechanism and Selectivity of the Phenol Synthesis

Abstract: The second phase of the gold-catalyzed phenol synthesis, the ring opening of the intermediate arene oxide, follows general acid catalysis. The product selectivity is determined by the substrate only and can be explained by the stability of the intermediate arenium ions. Thus, even remote substitutents can be used to control the chemoselectivity of the overall reaction by electronic influences and their influence is stronger than the steric influence of neighboring substituents. This is supported by quantum che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(91 citation statements)
references
References 24 publications
2
88
0
1
Order By: Relevance
“…The conversion of 15 o revealed a selectivity pattern that was comparable to earlier studies that concern furans with two additional substituents as nucleophiles in the furan-yne cyclization (Scheme 5). [4] As in the case of 15 n, the formation of six-ring annulated systems delivered considerably higher yields than five-membered derivatives. Here an overall yield of 89 % was obtained, which splits up into three different products.…”
Section: Resultsmentioning
confidence: 94%
“…The conversion of 15 o revealed a selectivity pattern that was comparable to earlier studies that concern furans with two additional substituents as nucleophiles in the furan-yne cyclization (Scheme 5). [4] As in the case of 15 n, the formation of six-ring annulated systems delivered considerably higher yields than five-membered derivatives. Here an overall yield of 89 % was obtained, which splits up into three different products.…”
Section: Resultsmentioning
confidence: 94%
“…[34][35][36] The gold-catalysed [37] rearrangement of furans with a pendant alkyne side-chain also gives phenols, but proceeds via an arene oxide rather than a Diels-Alder adduct. [38,39] A few examples of the Diels-Alder reactions of furans with electron-donating substituents at the 2-position and subsequent rearrangement to phenols have been reported. For example, as shown in Scheme 4, 2-methoxyfuran (9) was found to undergo a cycloaddition reaction with hexafluorobutyne (10) to give 11, which rearranges thermally, even in the absence of acid, to phenol 12.…”
Section: Lewis Acid Mediated Rearrangement Of 7-oxanorbornadienesmentioning
confidence: 99%
“…15 Remarkable works have also been performed regarding the elucidation of this mechanism including the successful isolation of several key intermediates, that is, the arene oxide and oxepine. 7,16 The breakage and formation of four bonds during this reaction is clearly not an elementary reaction. Because the rate-limiting step possesses lowest reaction rate in the overall reactions (reaction kinetic theory), the reaction intermediate of this step should be opulent and be detectable by the NMR, IR etc.…”
Section: Introductionmentioning
confidence: 99%
“…2 The Hashmi group showed that the reaction does not proceed via an alkynyl or a vinylidene complex because a primary kinetic isotope effect was not observed with a substrate deuterated at the alkyne. 16 The Echavarren group found that the intramolecular reaction of furans with alkynes catalyzed by PtCl 2 is mechanistically related to that of enyne in polar solvents. 13,14 The PtCl 2 -catalyzed reaction is initiated by the nucleophilic attack of the furan on a (h 2 -alkyne)-Pt(II) complex to form a cyclopropyl platinum carbene via density functional theory calculations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation